Effect of iodine supplementation in pregnant women on child neurodevelopment: a randomised, double-blind, placebo-controlled trial. Issue 11 (November 2017) - Gowachirapant, Sueppong; Jaiswal, Nidhi; Melse-Boonstra, Alida; Galetti, Valeria; Stinca, Sara; Mackenzie, Ian; Thomas, Susan; Thomas, Tinku; Winichagoon, Pattanee; Srinivasan, Krishnamachari; Zimmermann, Michael B
Summary: Background: Iodine deficiency during pregnancy might be associated with reduced intelligence quotient (IQ) score in offspring. We assessed the effect of iodine supplementation in mildly iodine-deficient pregnant women on neurodevelopment of their offspring in areas where schoolchildren were iodine sufficient. Methods: In this randomised, placebo-controlled trial, pregnant women in Bangalore, India, and Bangkok, Thailand, were randomly assigned (1:1) to receive 200 μg iodine orally once a day or placebo until delivery. Randomisation was done with a computer-generated sequence and stratified by site. Co-primary outcomes were verbal and performance IQ scores on the Wechsler Preschool and Primary Scale of Intelligence Third Edition (WPPSI-III) and the global executive composite score from the Behaviour Rating Inventory of Executive Function-Preschool Version (BRIEF-P) in the children at age 5–6 years. The trial was double-blinded; some unmasking took place at age 2 years for an interim analysis, but participants and nearly all investigators remained masked to group assignment until age 5–6 years. Analysis was by intention to treat using mixed-effects models. This trial is registered withClinicalTrials.gov, numberNCT00791466 . Findings: Between Nov 18, 2008, and March 12, 2011, 832 women entered the trial at a mean gestational age of 10·7 weeks (SD 2·7); median urinary iodine concentration was 131 μg/L (IQR 81–213). Mean compliance with supplementation was 87%, assessed by monthly tablet counts. 313 children (iodine group, n=159; placebo group, n=154) were analysed for verbal and performance IQ with WPPSI-III and 315 (iodine group, n=159; placebo group, n=156) for overall executive function with BRIEF-P. Mean WPPSI-III scores for verbal IQ were 89·5 (SD 9·8) in the iodine group and 90·2 (9·8) in the placebo group (difference −0·7, 95% CI −2·9 to 1·5; p=0·77), and for performance IQ were 97·5 (12·5) in the iodine group and 99·1 (13·4) in the placebo group (difference −1·6, −4·5 to 1·3; p=0·44). The mean BRIEF-P global executive composite score was 90·6 (26·2) in the iodine group and 91·5 (27·0) in the placebo group (difference −0·9, −6·8 to 5·0; p=0·74). The frequency of adverse events did not differ between groups during gestation or at delivery: 24 women in the iodine group and 28 in the placebo group reported adverse events (iodine group: abortion, n=20; blighted ovum, and n=2; intrauterine death, n=2; placebo group: abortion, n=22; blighted ovum, n=1; intrauterine death, n=2; early neonatal death, n=1; and neonatal death, n=2). Interpretation: Daily iodine supplementation in mildly iodine-deficient pregnant women had no effect on child neurodevelopment at age 5–6 years. Funding: Swiss National Science Foundation, Nestlé Foundation, Wageningen University and Research, and ETH Zurich.